Analisis Konteks Bahasa dalam Pembelajaran Bipa di Anuban Muslim Satun School Thailand - Sahrul Romadhon (Kelasa, 2018)
This research is more focused on Mattayum (high school) students at Anuban Muslim Satun School, Thailand. The problem faced by the teacher is to determine the appropriate method for teaching Indonesian at the school. This is because there are several factors, such as the strong influence of the Siamese language (native Thai language), it is not customary for learners to use Indonesian, and the strong influence of the Malay language which seems to be considered the same as Indonesian. This study uses a qualitative method of the type of grounded theory. Data analysis used structural analysis in accordance with the production of the language context written by students at Anuban Muslim Satun. The purpose of this study is to analyze the production of student writing. The results obtained from this study are recommendations on Indonesian language learning methods for Foreign Speakers (BIPA) based on language contexts. AbstrakPenelitian ini lebih difokuskan kepada pemelajar Mattayum (SMA) di Anuban Muslim Satun School, Thailand. Masalah yang dihadapi oleh pengajar adalah menentukan metode yang tepat untuk mengajarkan bahasa Indonesia di sekolah tersebut. Hal tersebut karena adanya beberapa faktor, seperti kuatnya pengaruh bahasa Siam (bahasa asli Thailand), tidak terbiasanya pemelajar menggunakan bahasa Indonesia, dan kuatnya pengaruh bahasa Melayu yang seolah-olah dianggap sama dengan bahasa Indonesia. Penelitian ini menggunakan metode kualitatif jenis grounded theory. Analisis data menggunakan analisis struktural sesuai dengan produksi konteks bahasa tulis pemelajar di Anuban Muslim Satun. Tujuan penelitian ini adalah untuk menganalisis produksi tulisan pemelajar. Hasil yang didapatkan dari penelitian ini adalah rekomendasi metode pembelajaran Bahasa Indonesia bagi Penutur Asing (BIPA) berbasis konteks bahasa.